2010
DOI: 10.1159/000320223
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Sorafenib in Elderly Patients Treated in the North American Advanced Renal Cell Carcinoma Sorafenib Expanded Access Program

Abstract: Objective: In this retrospective analysis of the Advanced Renal Cell Carcinoma Sorafenib (ARCCS) program in North America, we compared the safety and efficacy of sorafenib in patients aged ≧70 with those aged <70 years. Methods: Patients were treated with oral sorafenib twice daily until the occurrence of disease progression or treatment intolerance. The primary objective of the ARCCS program was making sorafenib available to patients with advanced renal cell carcinoma (RCC) in the USA and Canada before market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…In a population of advanced renal cell carcinoma patients aged ≥70 years, sorafenib was shown to be as safe and effective as in patients aged <70 years [23]. More recently, older populations with advanced HCC treated with sorafenib were compared with younger groups [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…In a population of advanced renal cell carcinoma patients aged ≥70 years, sorafenib was shown to be as safe and effective as in patients aged <70 years [23]. More recently, older populations with advanced HCC treated with sorafenib were compared with younger groups [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, it can also cause hematological abnormalities, including leukopenia, anemia, neutropenia and thrombocytopenia; and severe cardiovascular adverse event such as hypertensive crisis, myocardial ischemia and congestive heart failure. It has been reported that almost a third of the patients on a full dose of sorafenib (400 mg/BD) required a dose reduction and 10-17% of patients ceased treatment with the drug due to serious adverse events (8,13). Based on this, a combination treatment strategy with sorafenib and an agent that has synergistic effects is being evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…15 Insights into the safety and activity of sorafenib in a larger population of patients with advanced RCC were gathered from 2 expanded access programs prior to regulatory approval of sorafenib (the North America [NA-] and European [EU-] Advanced Renal Cell Carcinoma Sorafenib [ARCCS] studies). [16][17][18] Although the inclusion criteria for patients enrolled in these expanded access programs were broader than those used for the TARGET study, some exclusion criteria meant that the studied populations were not fully representative of patients encountered in routine clinical practice settings. For example, patients with cardiac arrhythmias, active coronary artery disease or ischemia, or uncontrolled hypertension were excluded from the NA-ARCCS, and < 1% of patients had received prior TKI therapy.…”
Section: Introductionmentioning
confidence: 99%